Effects of local versus remote ischemic preconditioning on repeated sprint running performance - Griffin, P. J.; Hughes, L.; Gissane, C.; Patterson, S. D. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: The aim of this study was to compare the effect of local and remote ischemic preconditioning (IPC) on repeated sprint exercise. METHODS: Twelve males (age 22±2 years; stature 1.79±0.07 m; body mass 77.8±8.4 kg; mean±SD) completed four trials consisting of remote (arm) and local (leg) IPC and SHAM interventions prior to repeated sprint exercise (3x[6x15+15-m] shuttle sprints), in a double-blind, randomized, crossover designed study. These tests were immediately preceded by IPC (4x5-minute intervals at 220 mmHg bilateral occlusion) or SHAM treatment (4x5-minute intervals at 20 mmHg bilateral occlusion). Sprint performance and percentage decrement score alongside measurement of Tissue Saturation Index, blood lactate and RPE were measured throughout the intervention. RESULTS: During the IPC/SHAM intervention there was a large decrease in TSI for IPC-arm in comparison to IPC-leg (P<0.05), however IPC-legs resulted in greater soreness compared with the other three conditions (P<0.05). There was no main effects or interaction effects for sprint performance. There was a significant effect of condition (P=0.047, r=0.56) on percentage decrement score across all 18 sprints with IPC demonstrating less fatigue than SHAM. There were no other effects of IPC during the sprint trials for any other physiological measure. CONCLUSIONS: In conclusion local IPC resulted in more pain/soreness during the IPC/SHAM intervention but both remote and local IPC reduced the fatigue associated with repeated sprint exercise.